DESIGN AND CONSTRUCTION OF MOBILE-BASED ONLINE MOTORCYCLE SERVICES - Suci Lestari Nasution, Winda; Nusa, Patriot (Journal of Computer Science and Technology (JCS-TECH), 2024)
Motorbike service is an activity of mechanics to repair vehicles that have problems in certain parts. Distance is a problem that makes people who want to repair a motorbike have to walk long distances to get to the motorbike service place. The aim of this online motorbike service is to help or make things easier for people. People who have problems with motorbikes that have quite a distance from home to the motorbike service place with a smartphone so that it is easy to make orders and payments can also use the payment method provided. The analysis and design method used in this research is Object Oriented Analysis and Design (OOAD) with the help of tools, namely Unified Modeling Language (UML). The results of this analysis and design will be implemented into a mobile-based application with features for ordering, paying, transaction history, determining location points, sending or receiving messages based on the results test well so that the feature runs properly.